Examining The Effects of Task Complexity and Task Difficulty on Students’ Knowledge Retention: A Cognitive Load Theory Perspective - Yulianto, Arief; Pramono, Suwito Eko; Wijaya, Angga Pandu; Lestari, Slamet; Putit, Lennora (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the effect of task complexity and task difficulty on knowledge retention through cognitive load. Previous studies have been largely outcome-oriented, focusing on student performance without examining long-term knowledge, thus leaving a gap for research that specifically elaborates on knowledge retention. A quantitative approach with a cross-sectional research design was employed. Using the Slovin formula with a 5% margin of error, the study involved 246 undergraduate students majoring in financial management from public universities located in Semarang, Surakarta, and Purwokerto, selected through purposive sampling. Data were analyzed using the variance-based structural equation modeling (VB-SEM) approach. The results reveal that cognitive load has a negative and significant effect on knowledge retention (β = -0.492, t = 4.167, p = 0.000). Task complexity shows a positive and significant effect on cognitive load (β = 0.300, t = 4.326, p = 0.000), but its direct effect on knowledge retention is not significant. Similarly, task difficulty has a positive and significant effect on cognitive load (β = 0.341, t = 4.628, p = 0.000), yet it does not directly affect knowledge retention. The findings indicate that both task complexity and task difficulty have negative and significant indirect effects on knowledge retention through cognitive load. These results demonstrate the importance of proportional instructional design, particularly the segmentation of complex content into smaller units to manage cognitive load. The use of educational technology is recommended to design tasks and instructional materials that align with students’ cognitive capacities, thereby enhancing knowledge retention.